SIMULASI DAN PERENCANAAN JARINGAN AIR BERSIH MENGGUNAKAN EPANET 2.2 PADA DESA KARANGLUHUR - Faqih, Nasyiin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2025)
Karangluhur Village, located in Kertek Subdistrict, Wonosobo Regency, has abundant spring water potential that remains underutilized. The community still relies on a single primary water source, while other springs cannot yet be used due to limited management. This study aims to design a clean water distribution network to meet the projected needs through 2039. The methods employed include exponential population projection (growth rate of 0.44%), calculation of water demand, planned discharge, pipe sizing, flow velocity, energy loss, and residual pressure. Data analysis was conducted using QGIS for elevation mapping and EPANET 2.2 for hydraulic simulation. The results show that the projected peak hour demand of 12.01 L/s can still be met by the available spring discharge of 22.38 L/s. The distribution network is designed using PVC pipes with diameters adjusted to flow requirements, achieving an average flow velocity of 0.77 m/s and a minimum residual pressure of 4.9 meters of water column (Mka). The system is expected to enhance the efficiency and equity of clean water distribution across the four main hamlets